Follow-Up After Cataract Surgery – Comparison of the Practice in Two Institutions with the Aim of Optimize the Routine - Westborg I (Dove Medical Press, 2020)
Inger Westborg, Eva Mönestam Department of Clinical Sciences/Ophthalmology, Faculty of Medicine, Umeå University, Umeå S-901 85, SwedenCorrespondence: Inger WestborgDepartment of Clinical Sciences/Ophthalmology, Faculty of Medicine, Umeå University, Umeå S-901 85, SwedenTel +46 70 6898498Fax +46 18 504857Email inger.westborg@akademiska.sePurpose: To evaluate the number of postoperative visits after cataract surgery in two institutions with different routines.Patients and Methods: A population-based prospective, observational, cohort study was conducted at two institutions in northern Sweden. All cataract surgery cases during a 1-year period were included. The study group was 1249 cases, who followed the standard routine at the Sunderby clinic, ie, no planned postoperative visit for patients without comorbidity who had uncomplicated surgery. All cases (n=1162) having surgery during the same 1-year period at the Umeå clinic were selected as the control group. The routine in Umeå was a planned postoperative visit for all patients after first eye surgery, and on second eye surgery patients with other ocular comorbidity.Results: A postoperative visit was planned in 44% (555/1249) of the study group and in 83% of all control group cases (966/1162). Significantly less patients in the study group (9% vs 16%; p=0.000036) initiated an unplanned contact. Patients with a distance to the hospital of 70 km or longer were less inclined to seek unplanned care (p=0.016). There was no difference in postoperative outcomes between the patients who initiated contact and those who did not in the study and control hospitals.Conclusion: Without compromising patient safety, it is possible to reduce the burden of postoperative visits in cases with uncomplicated cataract surgery. A reduction in the number of visits is obtained only if the standard routine is no planned postoperative visits in uncomplicated cases without ocular comorbidity for both first and second eye surgery.Keywords: cataract surgery, postoperative visits, patient-initiated contact, observational cohort study, safety aspects